Complications in facial plastic surgery - Capone, Randolph B.; Sykes, Jonathan M. (Thieme, 2012)
No one yearns to be associated with a complications text, nor wants notoriety as an expert in adverse outcomes. Yet complications occur, and are a fact of surgical practice. As the colloquial definition goes, an expert is one who is well versed in failure, and this certainly applies to the art and practice of surgery. Surgeons often learn more from the sting of a misstep than the satisfaction of a triumph. A text that is never far from reach in the resident call room is a surgical complications book, and the information contained within has helped countless surgeons on the wards, in the operating room, and at weekly morbidity conferences. This book provided motivation, in part, for the present work.